New challenges of crisis prevention : addressing economic imbalances in the North and boom-bust cycles in the South - Teunissen, Jan Joost (FONDAD The HagueNL, 2001)
Reflects on today's standard agenda of crisis prevention. Deals firstly with the possibilities for major industrial countries to address global economic imbalances, and secondly with how developing countries could counter boom-bust cycles.